The diagnostic accuracy of OCT angiography in naive and treated neovascular age-related macular degeneration: a review - Perrott-Reynolds, Rhianon; Cann, Robert; Cronbach, Nicola; Neo, Yan Ning; Ho, Vivian; McNally, Orla; Madi, Haifa A; Cochran, Claire; Chakravarthy, Usha (Eye (London), 2019)
Optical coherence tomography angiography (OCTA) is a non-invasive retinal imaging innovation that has been gaining popularity for the evaluation of the retinal vasculature. Of clinical importance is its current use either as an alternative or in conjunction with conventional dye-based angiography in neovascular age-related macular degeneration. OCTA is not without limitations and these include image artefact, a relatively small field of view and failure of the segmentation algorithms, which can confound the interpretation of findings. While there are numerous publications on OCTA in neovascular AMD, few have examined the diagnostic accuracy of this new technology compared with the accepted gold standard of fundus fluorescein angiography (FFA). In this review, we summarise the literature on the clinical application of OCTA in nAMD. In particular, we have reviewed the published articles that have reported the sensitivity and specificity of OCTA in the diagnosis of nAMD, and those that have described and or correlated the morphological findings and compared them to dye-based angiography.